Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 15. Beitrag. Hymenoptera: Myrmosidae und Mutillidae. - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The material, collected by the expedition of the Deutsches Entomologisches Institut in Albania represented 5 specimens of Myrmosidae (1 species) and 24 specimens of Mutillidae (10 species), 2 of which are new to the fauna of Albania. Now there are 2 species of the family Myrmosidae and 16 species of the family Mutillidae known from this country.